Smart feeding center design proposal for small breed dogs - Herrera-Gutiérrez, Bárbara Haydeé (2019)
BRUNO is a design project of an intelligent feeding and rest center for small breed dogs. This paper has the intention to explain broadly each design step that was followed while conceiving the Intelligent Feeding Center. Several design techniques such as needs finding has guided this industrial product into a wide market of a young pet owner user that characterizes itself for a 40 hour per week work schedule. His busy agenda affects his lifestyle specifically, when fulfilling the pet´s needs. This product will enclose the pet-owner relationship using different technological approaches.